Hubungan Antara Kinerja Karyawan Dengan Promosi Jabatan Pada Unit Taman Marga Satwa Ragunan Dinas Kehutanan Provinsi DKI Jakarta - dedy syahyuni (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Job performance is one of the ways used by the company to measure how well an employee in carrying out the work and tasks within the company. A good company will use performance as a benchmark the success of human resources management within the company.With a good performance measurement, the company can assess and ultimately improve the deficiencies in the work of the employees. Employees with good performance is an employee who can reach the expectations of the company.A growing number of employees who have good job performance can give benefit for the company. The company will have the good performance so effectiveness and efficiency can be achieved in the work. Effectiveness and efficiency from company, will make the cost of production decreases and eventually the company's earnings will rise.Therefore the company should give you a good appreciation for employees who have a good level of performance, one of them by providing promotional Office for employees. This paper tried to connect both of these variables, and calculation results obtained where there is a relationship of 0.729 And variable affects performance of 0.532 Key Word: job performance, job promotion, ragunan zoo